Fever in the tropics: aetiology and clinical profile of fever of unknown origin in children-a prospective observational study in a tertiary care hospital in South India - Sumathisri, Ramachandran; Pandi, Karuppiah; Srinivasan, Sadagopan (International Journal of Contemporary Pediatrics, 2019)
Background: Fever of unknown origin (FUO) is an important cause of morbidity and mortality in children, especially in tropical countries with varied aetiology and clinical presentation. Aim of this study is to determine the aetiology and outcome of FUO in Indian children. Study design is Prospective, observational study. Methods: We enrolled 75 children aged 1 to 12 years who were admitted with fever >8 days to the paediatric department from January 2015 to August 2016. Initial evaluation included complete blood count, peripheral smear, urine analysis, chest radiography, blood culture and tuberculin test. Results: In 72 children (96%), a definitive diagnosis could be established, whereas 3 children (4%) remained undiagnosed. Most common aetiology of FUO was infectious disease (90.6%) followed by malignancy (4%) and collagen vascular disease (1.3%). Among the infections group, scrub typhus was found to be the commonest aetiology (52%). Conclusions: Infections were the most common etiological factor for FUO in children aged 1-12 years of our region.